Fatigue crack propagation in short-fiber reinforced plastics (Fracture and Structural Integrity, 2015)
The influence of fiber orientation on the crack propagation behavior was studied with single edgenotchedspecimens which were cut from an injection-molded plate of short-fiber reinforced plastics ofpolyphenylenesulphide (PPS) reinforced with 30wt% carbon fibers. Specimens were cut at five fiber angles relative to the molding direction, i.e. ??= 0° (MD), 22.5°, 45°, 67.5°, 90° (TD). Fracture mechanics parameters derived based on anisotropic elasticity were used as a crack driving force. Macroscopic crack propagation path was nearly perpendicular to the loading axis for the cases of MD and TD. For the other fiber angles, the crack path was inclined because the crack tended to propagate along inclined fibers. For mode I crack propagation in MD and TD, the resistance to crack propagation is improved by fiber reinforcement, when the rate is correlated to the range of stress intensity factor. The crack propagation rate, da/dN, was slowest for MD and fastest for TD. For each material, the crack propagation rate is higher for larger R ratio. The effect of R ratio on da/dN diminished in the relation between da/dN and the range of energy release rate, ?GI. Difference among MD, TD and matrix resin becomes small when da/dN correlated to a parameter corresponding the crack-tip radius, H?GI, where H is compliance parameter. Fatigue cracks propagated under mixed loading of mode I and II for the fiber angles other than 0° and 90°. The data of the crack propagation rate correlated to the range of total energy release rate, ?Gtotal, lie between the relations obtained for MD and TD. All data of crack propagation tend to merge a single relation when the rate is correlated to the range of total energy release rate divided by Young’s modulus.
Keywords: Fatigue crack propagation